2007
DOI: 10.14238/pi47.4.2007.144-9
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of simplified Fencl-Stewart with Figge-Stewart method in diagnosing metabolic acidosis in critically ill children

Abstract: Background The traditional Henderson-Hasselbalch approach hasproven to be imprecise in critically ill patients. Stewart’s approachcan detect metabolic acidosis missed by traditional approach,including acidosis caused by increased unmeasured agreement(UA). The complexity of Stewart’s method leads to developmentof simpler modifications, simplified Fencl-Stewart and Figge-Stewart method. Agreement between both modifications isunknown.Objective This study aimed to measure the agreement of simplifiedFencl-Stewart w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The results of this research indicated a good suitability betweeen the simplified Fencl-Stewart method to Figge-Stewart method with a sensitivity of 80% and a specificity of 80%. In contrary, a research performed by Sinaga et al 24 showed an excellent suitability between the simplified Fencl-Stewart method and the Figge-Stewart method in diagnosing critical metabolic acidosis with a positive result agreement of 95.65% and a negative result agreement of 98.51%. 24 Meanwhile, a research conducted by Kurnia et al 25 comparing traditional method with the simplified Fencl-Stewart method in assessing the unmeasured anion as a cause of metabolic acidosis found a sensitivity of 94.3% and a specificity of 84%.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The results of this research indicated a good suitability betweeen the simplified Fencl-Stewart method to Figge-Stewart method with a sensitivity of 80% and a specificity of 80%. In contrary, a research performed by Sinaga et al 24 showed an excellent suitability between the simplified Fencl-Stewart method and the Figge-Stewart method in diagnosing critical metabolic acidosis with a positive result agreement of 95.65% and a negative result agreement of 98.51%. 24 Meanwhile, a research conducted by Kurnia et al 25 comparing traditional method with the simplified Fencl-Stewart method in assessing the unmeasured anion as a cause of metabolic acidosis found a sensitivity of 94.3% and a specificity of 84%.…”
Section: Resultsmentioning
confidence: 83%
“…In contrary, a research performed by Sinaga et al 24 showed an excellent suitability between the simplified Fencl-Stewart method and the Figge-Stewart method in diagnosing critical metabolic acidosis with a positive result agreement of 95.65% and a negative result agreement of 98.51%. 24 Meanwhile, a research conducted by Kurnia et al 25 comparing traditional method with the simplified Fencl-Stewart method in assessing the unmeasured anion as a cause of metabolic acidosis found a sensitivity of 94.3% and a specificity of 84%. On the other hand, in comparing traditional method with the Figge-Stewart method in assessing the unmeasured anion, the reserach showed a sensitivity of 100% and a specificity of 76%.…”
Section: Resultsmentioning
confidence: 83%
“…5 The lack of this method is the dependence of HCO 3 -serum level toward PaCO 2 and it is difficult to detect acid-base imbalance in complex metabolic situations especially for critically ill patients. 4,6 Siggaard-Anderson completed Henderson-Hasselbalch equation with BE calculation. Base excess is the amount of acid or alkali that have to be added into 1 L of whole blood to balance blood pH to be 7.4 in PaCO 2 40 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Alternative method (Stewart) is difficult to apply because it has many variables that have to be measured and calculated so the experts developed a simplified Stewart method including Fencl-Stewart and Figge-Stewart. 6,11,12 Fencl-Stewart method calculates BDE gap based on Na + , Cland albumin concentrations. Figge-Stewart method calculated SIG (the difference between apparent SID/ SIDa and effective SID/SIDe) showing there are other unmeasured strong ions.…”
Section: Methodsmentioning
confidence: 99%